Prenatal Maternal Anxiety in South Asia: A Rapid Best-Fit Framework Synthesis - Bright, Katherine Stuart; Norris, Jill M.; Letourneau, Nicole L.; King Rosario, Melanie; Premji, Shahirose S. (Frontiers in Psychiatry, 2018)
Background Most research efforts towards prenatal maternal anxiety has been situated in high-income countries. In contrast, research from low- and middle-income countries has focused on maternal depression and prenatal maternal anxiety in low- and middle-income countries remains poorly understood. Objectives To examine whether current prenatal maternal anxiety measurement tools capture dimensions of anxiety during pregnancy that are experienced by women in South Asia. Design We conducted a rapid review with best fit framework synthesis, as we wished to map study findings to an a priori framework of dimensions measured by prenatal maternal anxiety tools. Data sources We searched MEDLINE, PsycINFO, and CINAHL and grey literature in November 2016. Studies were included if published in English, used any study design, and focused on women’s experiences of prenatal/antenatal anxiety in South Asia. Review methods Study quality was assessed using the Effective Public Health Practice Project Quality Assessment Tool and Critical Appraisal Skills Programme Qualitative Checklist. Study findings were extracted to an a priori framework derived from pregnancy-related anxiety tools. Results From 4177 citations, 9 studies with 19,251 women were included. Study findings mapped to the a priori framework apart from body image. A new theme, gender inequality, emerged from the studies and was overtly examined through gender disparity, gender preference of fetus, or domestic violence. Conclusions Gender inequality and societal acceptability of domestic violence in South Asian women contextualizes the experience of prenatal maternal anxiety. Pregnancy-related anxiety tools should include domains related to gender inequality to better understand their influence on pregnancy outcomes.